Waist-to-height ratio identifies children with lower physical activity and reduced cardiorespiratory fitness: Longitudinal evidence from Norwegian primary schools – The Health Oriented Pedagogical Project (HOPP) - Per Morten Fredriksen; Nandu Goswami; Asgeir Mamen (PLoS ONE, 2026)
Objectives Childhood obesity and physical inactivity are major global health concerns because of their links to cardiometabolic risk factors that may persist into adulthood. Waist-to-height ratio (WHtR) has emerged as a practical indicator of central adiposity and metabolic risk. Moderate-to-vigorous physical activity (MVPA) and cardiorespiratory fitness are important factors in reducing obesity-related risk. This study investigated the association between WHtR, physical activity, and fitness in children aged 6–12 years. Methods The Health Oriented Pedagogical Project (HOPP) is a longitudinal cohort study conducted from 2015 to 2020 and including 2297 Norwegian children. WHtR was examined as the main time-varying exposure. Separate linear mixed models were fitted for MVPA, sedentary time, Andersen intermittent running test performance, and VO₂peak as outcomes, with age, sex, and socioeconomic status included as covariates. Results Each 0.1 unit increase in WHtR was linked to a −0.62 min/day reduction in average MVPA. Higher WHtR was associated with lower MVPA and lower cardiorespiratory fitness, including both Andersen test performance and VO₂peak. No clear association was observed between WHtR and sedentary time. Conclusion In this longitudinal cohort, higher WHtR was associated with lower physical activity and lower cardiorespiratory fitness. WHtR may therefore serve as a simple screening indicator for identifying children who may warrant closer assessment of fitness, physical activity, and cardiometabolic risk.